2006
DOI: 10.1063/1.2221905
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nanoparticle clustering and alignment on thermal conductivities of Fe3O4 aqueous nanofluids

Abstract: Thermal conductivities of Fe3O4 aqueous nanofluids were studied. The results show that Fe3O4 nanofluids have higher thermal conductivities than other oxide aqueous nanofluids at the same volume fraction. The experimental values are higher than those predicted by the existing models. The abnormal thermal conductivities of Fe3O4 nanofluids are attributed to the observed nanoparticle clustering and alignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
126
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(135 citation statements)
references
References 16 publications
8
126
0
1
Order By: Relevance
“…13 It was also shown that at the same volume fractions, Fe 3 O 4 nanofluids have higher thermal conductivity than other metal oxide nanofluids such as CuO, TiO 2 , and Al 2 O 3 as a result of nanoparticle alignment. 26 Although the thermal conductivity of aqueous nanofluids increases, while that of non-aqueous nanofluids decreases with temperature, the ratio of the nanofluid thermal conductivity to base fluid thermal conductivity remains constant, 25,27 implying that the temperature dependency of thermal conductivity does not change upon addition of nanoparticles. This enhancement in thermal conductivity was found to be higher 19,26 than predictions by the effective medium theory (EMT) proposed by Maxwell 28 and other theoretical models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 It was also shown that at the same volume fractions, Fe 3 O 4 nanofluids have higher thermal conductivity than other metal oxide nanofluids such as CuO, TiO 2 , and Al 2 O 3 as a result of nanoparticle alignment. 26 Although the thermal conductivity of aqueous nanofluids increases, while that of non-aqueous nanofluids decreases with temperature, the ratio of the nanofluid thermal conductivity to base fluid thermal conductivity remains constant, 25,27 implying that the temperature dependency of thermal conductivity does not change upon addition of nanoparticles. This enhancement in thermal conductivity was found to be higher 19,26 than predictions by the effective medium theory (EMT) proposed by Maxwell 28 and other theoretical models.…”
Section: Introductionmentioning
confidence: 99%
“…26 Although the thermal conductivity of aqueous nanofluids increases, while that of non-aqueous nanofluids decreases with temperature, the ratio of the nanofluid thermal conductivity to base fluid thermal conductivity remains constant, 25,27 implying that the temperature dependency of thermal conductivity does not change upon addition of nanoparticles. This enhancement in thermal conductivity was found to be higher 19,26 than predictions by the effective medium theory (EMT) proposed by Maxwell 28 and other theoretical models. 29 On the other hand, Timofeeva et al 10,30 Based on specific experimental data, some empirical models were also presented.…”
Section: Introductionmentioning
confidence: 99%
“…Among these additives, oxide nanoparticles [5][6][7][8] consitute one of the important classes. In order to investigate the thermal transport properties of nanofluids containing oxide nanoparticles, five kinds of nanofluids were prepared and the measurement techniques and conditions were the same in order to ensure consistency of the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Heat conduction in nanofluids has been extensively studied, [9][10][11][12][13][14][15][16] and the variation in results has led to much debate as to the mechanisms of thermal conduction in nanofluids. By freezing nanofluids consisting of alumina nanoparticles in different base fluids, Gao et al 16 demonstrated that clustering is a key factor for enhancing the thermal conductivity.…”
mentioning
confidence: 99%